Word formation of slang used in selected songs of SZA’s sos album - Syahidah, Nuha Nur (Journal of Language and Pragmatics Studies, 2024)
This research concerns word formation processes of slang in selected songs of SZA’s SOS Album which are “SOS,” “Snooze,” and “Low.” This research aims to: 1) analyze the types of word formation of slang words based on Yule's theory utilized in selected songs 2) analyze their meaning, and 3) analyze which songs, word-formation processes, and slang words dominate and are used most frequently. This research uses a descriptive qualitative method. This research also uses observation as a method of data collection and distributional methods to analyze the data. The theory uses in this research is Yule’s theory (2006) of the word formation process. This research concludes that there are 149 times Slang words that appear in selected songs of SZA's album SOS, with "SOS" appearing 41 times, “Low” 73 times, and "Snooze” 35 times. The types of word formation processes found are blending 95 times or 63.8%, clipping 30 times or 20.1%, compounding 13 times or 8.7%, coinage 9 times or 6%, and acronyms and derivation each 1 time or 0.7%. It also concludes that "I'm" is the most frequently used slang word, appearing 38 times.